Effectiveness of Progressive Muscle Relaxation and Benson Spiritual Care on Reducing Fatigue in Patients with Type 2 Diabetes Mellitus - Sri Surani; Uswatun Hasanah; Tria Astika; Fitrian Rayasari (Indonesian Journal of Global Health Research, 2025)
Multifactorial fatigue syndrome is a symptom often felt by people with type 2 diabetes mellitus. Fatigue can prevent someone from doing daily activities that support glucose control. Progressive muscle relaxation and Bensonspiritual careis a combination of relaxation to reduce fatigue. This study was to determine the effectiveness of the combination of progressive muscle relaxation and Bensonspiritual careon fatigue in patients with type 2 diabetes mellitus. Research design using designQuasy Experimental pre test – post test control group designand techniquespurposive sampling. The sample of this study consisted of 2 groups, namely intervention and control, each with 24 respondents. The sampling technique used is purposive sampling. Fatigue was measured using the Indonesian Multidimensional Fatigue Inventory (IMFI-20). There was a decrease in fatigue with the combination of progressive muscle relaxation and Bensonspiritual care with the average fatigue value decreasing significantly (-59.5) compared to the control group (-16.8). The results of the independent t-test obtained ap value <0.001, there was a difference in the average fatigue (difference) between the intervention group and the control group. The study concluded that there was a combined effect of progressive muscle relaxation and Bensonspiritual care on reducing fatigue in patients with type 2 diabetes mellitus. Interventions can be developed as independent nursing interventions in patients with type 2 diabetes mellitus with fatigue.